2008
DOI: 10.1007/s00414-008-0250-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of number of loci on geographical structuring and forensic applicability of Y-STR data in Finland

Abstract: The Y-chromosomal diversity among Finnish males is characterized by low diversity and substantial geographical substructuring. In a 12-locus data set (PowerPlexY), especially the eastern parts of the country showed low levels of variation, and the western, middle, and eastern parts of Finland differed from each other by their Y-short tandem repeat (STR) haplotype frequencies (Palo et al., Forensic Sci Int Genet 1:120-124, 2007). In this paper, we have analyzed geographical patterns of Y-STR diversity using bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…Altogether, the newly developed typing methods applied to the Turku sample yielded results, which are in accordance with previous observations on Finnish Ychromosomal lineages [25,28,29,32,34]. Decreasing the volume of a SNP typing assay in the described manner leads to high-quality results comparable to those observed with conventional typing assays.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Altogether, the newly developed typing methods applied to the Turku sample yielded results, which are in accordance with previous observations on Finnish Ychromosomal lineages [25,28,29,32,34]. Decreasing the volume of a SNP typing assay in the described manner leads to high-quality results comparable to those observed with conventional typing assays.…”
Section: Resultssupporting
confidence: 89%
“…However, western provinces have shown higher Y-chromosomal HT diversity than the middle and eastern parts [29], and it is still lower than in other Scandinavian [30] or in other European populations [31]. Analysis of a greater number of Y-STR loci has been shown to significantly increase the HT diversity and to lower the level of interregional differentiation in the Finnish population; nevertheless, discrimination power is relatively low [32]. The most common HT found in the Turku sample is abundant in the Uralic-Yukaghir metapopulation according to the Y chromosome haplotype reference database (YHRD) [33] and is also observed predominantly in the north and east of Europe, i.e., Norway, Sweden (Swedish Saami [30]), Estonia, Lithuania, Belarus, and the Russian Federation, but to a much lesser extent.…”
Section: Resultsmentioning
confidence: 90%
“…Because of environmental destruction and the scarcity of forensic samples, incomplete Y-STR profiles are often obtained from trace evidence material or mixed male/female samples in forensic casework. The DYS19, DYS389II, DYS448, and DYS635 loci have been reported to be among the most frequent noninformative loci, followed by DYS385a/b, DYS390, DYS392, DYS437, and DYS438 in the 17 Y-STRs system [6,14,15]. Loss of the signals will decrease the discrimination capacity.…”
Section: Introductionmentioning
confidence: 95%
“…Y haplotype distributions in different population groups and varied types of markers have been widely reported. Extensive large-scale population surveys have been carried out and are still ongoing to increase the forensic databases [3][4][5][6][7]. Population genetic diversity in relation to microsatellite heterogeneity has been investigated to trace human evolution and migration, and phylogenetic trees or multidimensional scaling (MDS) plots based on Y-STR have been described [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown (34) that commercially available kits like PowerPlex Y or Yfiler cannot provide a sufficient discrimination power to discern the haplotypes inside broad families, and a definition of a region-specific set of Y-STR loci is a must. The results of haplotype diversity of the population samples tested within this study (VALACH, VLIN, and CZE) revealed that the sampling in one close geographic region or inside a group of people that recognize themselves as members of a certain “clan” brings lower diversity.…”
Section: Discussionmentioning
confidence: 99%